Inositol hexakisphosphate increases the size of platelet aggregates - Brehm, M; Klemm, U; Rehbach, C; Erdmann, N; Kolšek, K; Lin, H; Aponte-Santamaría, C; Gräter, F; Rauch, B; Riley, A; Mayr, G; Potter, B; et al. (Elsevier, 2018)
The inositol phosphates, InsP5 and InsP6, have recently been identified as binding partners of fibrinogen, which is critically involved in hemostasis by crosslinking activated platelets at sites of vascular injury. Here, we investigated the putative physiological role of this interaction and found that platelets increase their InsP6 concentration upon stimulation with the PLC-activating agonists thrombin, collagen I and ADP and present a fraction of it at the outer plasma membrane. Cone and plate analysis in whole blood revealed that InsP6 specifically increases platelet aggregate size. This effect is fibrinogen-dependent, since it is inhibited by an antibody that blocks fibrinogen binding to platelets. Furthermore, InsP6 has only an effect on aggregate size of washed platelets when fibrinogen is present, while it has no influence in presence of von Willebrand factor or collagen. By employing blind docking studies we predicted the binding site for InsP6 at the bundle between the γ and β helical subunit of fibrinogen. Since InsP6 is unable to directly activate platelets and it did not exhibit an effect on thrombin formation or fibrin structure, our data indicate that InsP6 might be a hemostatic agent that is produced by platelets upon stimulation with PLC-activating agonists to promote platelet aggregation by supporting crosslinking of fibrinogen and activated platelets.